2015
DOI: 10.1080/2162402x.2015.1049802
|View full text |Cite
|
Sign up to set email alerts
|

Cryoablation and Meriva have strong therapeutic effect on triple-negative breast cancer

Abstract: Keywords: adjuvant, cryoablation, immunogenic tumor cell death, Mage-b, Meriva, metastatic breast cancer, Survivin, triple-negative breast cancer, vaccinesInterleukin-6, a cytokine produced particularly by triple-negative breast cancers, strongly inhibits T cell responses in the tumor microenvironment. Here we tested cryoablation combined with Meriva (a lecithin delivery system of curcumin with improved bioavailability) in mice with metastatic breast cancer (4T1). Cryoablation involves killing of tumor cells t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 42 publications
0
12
1
Order By: Relevance
“…Several studies have observed changes in inflammatory biomarkers upon curcumin intake. The absence of changes in inflammatory biomarker levels seems contradictory to other studies where CP treatment has shown to decrease the levels of several inflammatory markers such as CRP (25), IL-1β (41), IL-6 (8, 41, 42), IL-22 (43), sCD40L (41). However, in our study, the levels of a substantial number of analytes were below the detection limit, so further decreases cannot be detected.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Several studies have observed changes in inflammatory biomarkers upon curcumin intake. The absence of changes in inflammatory biomarker levels seems contradictory to other studies where CP treatment has shown to decrease the levels of several inflammatory markers such as CRP (25), IL-1β (41), IL-6 (8, 41, 42), IL-22 (43), sCD40L (41). However, in our study, the levels of a substantial number of analytes were below the detection limit, so further decreases cannot be detected.…”
Section: Discussioncontrasting
confidence: 70%
“…Curcumin has been shown to inhibit the accumulation of myeloid-derived suppressor cells (MDSC) and their interaction with cancer cells and induces the differentiation/maturation of MDSC (7). Curcumin reduced intratumoral IL-6 production and metastasis formation in a breast cancer model and, when combined with cryoablation, induced robust anti-tumor T cell immunity and reduced tumor growth (8). In RAW 264.7 murine macrophages, a curcumin formulation significantly decreased the LPS-induced pro-inflammatory mediators NO, PGE 2 , and IL-6 by inhibiting activation of NF-κB (9).…”
Section: Introductionmentioning
confidence: 99%
“…For example, curcumin has been used for millennia because it improves immunity against cancer. Interestingly, experimental studies in mice have demonstrated significant inhibition of tumor growth after combining curcumin with percutaneous cryoablation [20]. These results are supported by several preclinical and clinical studies demonstrating that percutaneous ablations combined with appropriate immunomodulators can induce a therapeutically effective systemic anti-tumor immune response [21].…”
Section: Naturopathic Medicinementioning
confidence: 90%
“…More importantly, it is a repeatable procedure in case of local relapse or incomplete ablation. Furthermore, it does not interrupt other systemic therapies, ie, systemic treatment for metastatic disease, and can act in synergy with them 1,19,20. Cryoablation is not without possible adverse effects.…”
Section: Cryoablation Technique and Application In Breast Cancermentioning
confidence: 99%